Quantification of SARS‐CoV‐2 viral load in patients using time‐to‐results in antigen lateral flow tests - Elsa W. Braunstein; Eric Vail; David D. Ho; Lihong Liu; Hiroshi Mohri; Matthew Gayhart; Glenn D. Braunstein (Wiley, 2024)
Abstract Based upon clinical observations and recent reports, we anticipated there would be an inverse dose-response relationship between the severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) viral load and the time‐to‐positivity after application of the nasal swab sample in two popular home coronavirus disease 2019 (COVID‐19) antigen tests, BinaxNOW COVID‐19 Antigen Self‐Test and Flowflex COVID‐19 Antigen Home Test, both of which are sensitive to the nucleocapsid protein (NP). The relationship among the concentration of NP, WA1, and Omicron XBB.1.5 viral strains and the time‐to‐positive result by visual assessment in the tests was examined. The correlation between reverse transcription‐polymerase chain reaction cycle threshold (Ct) values and time‐to‐positivity in clinical samples (training set) also was determined. Strong inverse correlations were obtained between the concentration of the NP, WA1, XBB.1.5, Ct values for dilutions of both WA1 and XBB.1.5, as well as Ct values from the clinical samples and time‐to‐positivity in both antigen tests. The correlation between the actual and predicted Ct values interpolated from the training set was high with both tests in a second set of clinical samples. These results, together with those of other investigations with similar tests, suggest that the time‐to‐positive visual result in most, if not all, lateral flow COVID‐19 antigen tests can be utilized to estimate SARS‐CoV‐2 viral concentrations.